EMPAT LANGKAH STRATEGIS MEMBANGUN KUALITAS PENDIDIKAN VOKASI DAN KEJURUAN DI INDONESIA - Murnomo, Agus (Universitas Negeri Semarang, 2010)
The term technical and vocational education is introduced in the Law No. 20 of2003 on National Education System. The concept of technical and vocationaleducation emphasizes on education which ensures that students have a specificexpertise and job. The government hopes that graduates of a technical and vocationaleducation become work forces who have life skills which are relevant to the jobmarket demand. In order to realize the expectation quality improvement ontechnical and vocational education is needed. Some issues which have to be takeninto account regarding the quality improvement of technical and vocationaleducation are that: (1) the administrartion must be supported by the administratingorganization, local and central government, (2) the curriculum is competencebased,(3) the administration is developed in line with the local potentials, (4) andthe administration must involve business/industry. The success of theadministration of technical and vocational education will lessen the stateseconomical burden. On the contrary, if it fails, it will increase the number ofunemployment which will worsen the states economy.Kata kunci: kualitas pendidikan, pendidikan vokasi, kejuruan